MEDIA E-FLIPBOOK MENGENAI AKTIVITAS FISIK DALAM UPAYA PENCEGAHAN DIABETES MELITUS TIPE 2 DI SMKN 1 KARANG TENGAH CIANJU - alya, intan; Karjatin, Atin (Jurnal Kesehatan Siliwangi, 2024)
Background: The prevalence of diabetes mellitus in the population aged 15 years and over increased from 6.9% in 2013 to 10.9% in 2018. 1 Efforts to prevent and control diabetes mellitus are very important, especially regarding knowledge, awareness and motivation to change lifestyles towards a healthier and better direction, for example by doing physical activity.. Based on the results of research (Aisyah, 2023),e-flipbook educational media can increase student knowledge, motivation, learning interest, concept understanding, and learning outcomes. Objective: To determine the feasibility of e-flipbook educational media about the prevention of diabetes mellitus regarding physical activity in students with a 4D approach. Methods: The research method uses a 4D approach: define, design, development (material test, media, small scale, quantitative statistical test on Pre-Experiment One Group Pretest Posttest with 81 students), and dissemination.Results: The results of a preliminary study of 13 respondents who had filled out a questionnaire stated that they had never received education about diabetes mellitus related to physical activity and 10 out of 13 respondents were interested in education about physical activity using e-flipbook media, e-flipbook media Designed with a size of 21x 42 cm consisting of 20 pages and then converted into a digital flipbook, the development of media is feasible to use and the influence on knowledge. media can be accessed through links and QR codes. Conclusion: E-flipbook educational media is worth using and can be accessed through https://heyzine. com/flip- book/e47e2989c9. html link